THE IMPACT OF PROJECT-BASED LEARNING ON IMPROVING CRITICAL THINKING SKILLS AND TECHNOLOGICAL LITERACY IN LISTENING CLASS - Wawan Setyawan; Lina Saptaria (Program Studi PGSD Universitas Flores, 2025)
Vocational high school students need e-modules as innovative media in project-based learning (PBL) to develop critical thinking skills and technological literacy skills. This study aims to analyze the impact of e-modules applied in project-based learning on technological literacy skills and critical thinking skills of vocational high school students in KNX-based Smart Building System Learning, which has not been widely studied. The type of research is an experiment with a quantitative approach. The population of this study was all grade XII students at SMK Negeri 1 Kediri, with 60 respondents. The instruments used were tests and observation sheets to measure critical thinking skills and technological literacy skills. The data collection technique used observation assessments by two expert observers and through tests (pretest and posttest). The data analysis technique used the N-Gain score test and the independent sample t-test using SPSS. The results of the two observers' assessment of the quality of learning were excellent. The results of the independent sample t-test showed that there was a significant difference between student learning outcomes in the pretest and posttest data. The results of the N-Gain score test showed that learning practices were quite effective in improving students' critical thinking skills and literacy skills. This study is helpful in developing the insights of vocational high school teachers in KNX-based Smart Building System learning innovations.